Differential protein expression in chicken macrophages and heterophils in vivo following infection with Salmonella Enteritidis - Sekelova, Zuzana; Stepanova, Hana; Polansky, Ondrej; Varmuzova, Karolina; Faldynova, Marcela; Fedr, Radek; Rychlik, Ivan; Vlasatikova, Lenka (Veterinary research, 2017)
In this study we compared the proteomes of macrophages and heterophils isolated from the spleen 4 days after intravenous infection of chickens with Salmonella Enteritidis. Heterophils were characterized by expression of MMP9, MRP126, LECT2, CATHL1, CATHL2, CATHL3, LYG2, LYZ and RSFR. Macrophages specifically expressed receptor proteins, e.g. MRC1L, LRP1, LGALS1, LRPAP1 and a DMBT1L. Following infection, heterophils decreased ALB and FN1, and released MMP9 to enable their translocation to the site of infection. In addition, the endoplasmic reticulum proteins increased in heterophils which resulted in the release of granular proteins. Since transcription of genes encoding granular proteins did not decrease, these genes remained continuously transcribed and translated even after initial degranulation. Macrophages increased amounts of fatty acid elongation pathway proteins, lysosomal and phagosomal proteins. Macrophages were less responsive to acute infection than heterophils and an increase in proteins like CATHL1, CATHL2, RSFR, LECT2 and GAL1 in the absence of any change in their expression at RNA level could even be explained by capturing these proteins from the external environment into which these could have been released by heterophils.
Keywords: Real-Time Polymerase Chain Reaction; průtoková cytometrie; Salmonella enteritidis; nemoci drůbeže; Gene Expression Regulation; kur domácí; protilátky heterofilní; kvantitativní polymerázová řetězová reakce; regulace genové exprese; Flow Cytometry; Macrophages; Chickens; Proteome; zvířata; Poultry Diseases; makrofágy; Antibodies, Heterophile; proteom; salmonelová infekce u zvířat; Salmonella Infections, Animal; Animals